SHAFI?I USUL THOUGHT IN LATE THIRD-CENTURY AH: EDITION, TRANSLATION, AND INTERPRETATION OF CHAPTERS ON USUL AL-FIQH IN AL-WADA?I? - (:unkn) unknown (My University, 2016)
0

Ibn Surayj, a prominent figure in the formative period of the Shafi?i law school, has played an important role in both the transformation of Shafi?i substantive law and the development of early Islamic legal theory. Ibn Surayj reportedly wrote approximately four hundred works, few of which are extant today. Thanks to his contribution to the school, he is known as "the second al-Shafi?i (al-Shafi?i al-saghir);" indeed, according to some modern scholars, Ibn Surayj is the true founder of the Shafi?i school and Islamic legal theory. Although Ibn Surayj's works on Islamic law are no longer available, the later chapters of al-Wada?i? li-mansus al-shara?i?, one of his two extant works, bear the following titles: abrogation (naskh), prophetic traditions (sunan), singletransmitter report (khabar al-wahid), consensus (ijma?), analogy (qiyas), and knowledge (?ilm). This study presents the edition and translation of relevant titles in al-Wada?i? to provide Ibn Surayj's views on usul. In addition, this paper discusses Ibn Surayj's place in the evolution of Islamic legal theory, and how Ibn Surayj interprets alShafi?i's understanding of usul.
Keywords: Din Bilimi